Synthesis of PTSH-modified CeO2 nanoparticles: Effect of the modifier on structure, optical properties, and dispersibility - Truffault, Laurianne; Andrezza, Caroline; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP] (Elsevier, 2013)
CeO2 nanoparticles were synthesized by the precipitation method and modified with para-toluene sulfonic acid (PTSH), either in situ or post-synthesis. The presence of PTSH in the samples was confirmed by FTIR. PXRD and FTIR analyses showed that the post-synthesis PTSH modification altered the CeO2 structure, whereas the in situ modification maintained intact the crystalline structure and UV-vis absorbance properties. For both in situ and post-synthesis modifications, TEM images revealed the presence of nanoparticles that were 5nm in size. The dispersibility of the in situ PTSH-modified material in a hydrophilic ureasil-poly(ethylene oxide) matrix was investigated using SAXS measurements, which indicated that CeO2 nanoparticles modified with PTSH in situ were less aggregated within the matrix, compared to unmodified CeO2 nanoparticles. © 2013 Elsevier B.V.
Keywords: CeO2 nanoparticles; Dispersibility; Surface modification; Crystalline structure; Dispersibilities; Ethylene oxides; FTIR analysis; Post-synthesis modification; Precipitation methods; Situ modification; UV-vis absorbance; Nanoparticles; Optical properties; Polyethylene oxides; Precipitation (chemical); Surface treatment; Synthesis (chemical); 4 toluene sulfonic acid; cerium oxide; macrogol; nanoparticle; sulfonic acid derivative; titanium dioxide; toluene; unclassified drug; infrared spectroscopy; priority journal; synthesis; transmission electron microscopy; ultraviolet radiation